The effect of additives on tribological behaviours in polyurea grease. (May 2015) - Wen, M. Y.; Guo, P.; Hui, J. D.; Hui, Z. M.; Geng, F.
<x content-type="archive" xml:space="preserve">Abstract</x> Graphite, fluorography polymer, polytetrafluoroethylene, molybdenum disulphide and hexagonal boron nitride were used as additives for making polyurea grease. The effects of different additives and combinations of additives on the properties of polyurea grease were investigated. The advanced polyurea greases were prepared by optimising the composition ratio. The prepared polyurea grease showed high-dropping point, oxidation stability, corrosion resistance, anti-water drenching, anti-wear and extreme pressure properties.